The compatibility of deformation of the hollow-core slab with beams - Alexandr Koyankin; Valery Mitasov; Sergey Deordiev (Inzhenerno-stroitelʹnyĭ zhurnal, 2019)
The features of deformation of the key joint of a hollow core slab with precast-monolithic (monolithic) beam of a frame constructive system, including the Saret series. Experimental studies have been performed and numerical research of the stress-strain state of the slab and beam precast monolithic frame joint are carried out. Based on the obtained data, a comparative analysis of the results of numerical studies with experimental research has been performed, which showed a satisfactory convergence of results. As a result of the conducted researches new data concerning design features of the joint of the hollow slab with the beam have been obtained. Conclusions are given about the bearing capacity, stiffness and crack resistance of the structural solution of the joint node. The “weak points” associated with the design and operation of the joint of the slab with the beam are indicated. Technical solutions have been proposed to address the identified shortcomings, such as installation of the upper reinforcement in the hollow plate in longitudinal and transverse directions or exclusion of the key rigid joint to improve the structural reliability of the building.